2005
DOI: 10.1002/cphc.200400653
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Fluorescence Depolarisation in the Yellow Fluorescent Protein due to Its Dimerisation

Abstract: Transient absorption spectroscopy with sub-100 fs time resolution was performed to investigate the oligomerisation behaviour of eYFP in solution. A single time constant tau(AD)=2.2+/-0.15 ps is sufficient to describe the time-resolved anisotropy decay up to at least 200 ps. The close contact of two protein barrels is deduced as the exclusive aggregation state in solution. From the final anisotropy r(infinity)=0.28+/-0.02, the underlying quaternary structure can be traced back to the somewhat distorted structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 92 publications
(122 reference statements)
6
32
0
Order By: Relevance
“…In fact, dimerization has been observed for GFP (18) and YFP (4,19) at high concentrations. Jung et al reported a final anisotropy of 0.28 ± 0.02 following an ultrafast fluorescence depolarization in YFP upon direct excitation of the anionic chromophore, as a result of homo-FRET between two identical, anionic chromophores in a YFP dimer (20). Aside from emission-reabsorption and homo-FRET, other concentration-dependent processes may also exist and cannot be ruled out.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, dimerization has been observed for GFP (18) and YFP (4,19) at high concentrations. Jung et al reported a final anisotropy of 0.28 ± 0.02 following an ultrafast fluorescence depolarization in YFP upon direct excitation of the anionic chromophore, as a result of homo-FRET between two identical, anionic chromophores in a YFP dimer (20). Aside from emission-reabsorption and homo-FRET, other concentration-dependent processes may also exist and cannot be ruled out.…”
Section: Resultsmentioning
confidence: 99%
“…As there is only a small conformational change upon binding of Zn(II) to the low-affinity site, we can allow only solutions with small changes in all involved angles. Furthermore, the EYFP absorption dipole moment has been defined, 51,52 and the ECFP emission dipole moment is expected to lie within the plane of the chromophore. Using the proposed conformation of the Zn(II)-bound complex in which both Cys39 and both Cys208 are in close proximity (Figure 10(b)), there is only one solution that satisfies all these criteria (Figure 10(a)).…”
Section: Structural Understanding Of Emission Ratio Changesmentioning
confidence: 99%
“…Finally, the tendency of many fluorescent proteins to form dimers and tetramers [35,[91][92][93] can lead to complex energy-transfer interactions between the proteins within the oligomer [86,92,94].…”
Section: General Structure Of Vfpsmentioning
confidence: 99%